Effect of reduced glutathione on follicle stimulating hormone levels and spermatozoon quality of adult rat exposed to monosodium glutamate administration - Kartika, Ayla; Oenzil, Fadil; Anas, Eliza (International Journal of Research in Medical Sciences, 2018)
Background: Excessive consumption of Monosodium Glutamate (MSG) causes oxidative stress of hypothalamic cells and testicular cells thus affecting the process of spermatogenesis. Reduced Glutathione (GSH), as an antioxidant can reduce oxidative stress. This study aimed to see the effect of GSH on Follicle Stimulathing Hormone (FSH) levels and the quality of spermatozoon in male rats given MSG. Methods: This research used experiment with post test only control group design. The samples used were 27 male rats divided into 3 groups. The negative control group (KN) was given a standard diet, the positive control group (KP) was given MSG 144mg/200grbw, the treatment group (P) was given a standard diet and MSG dose was 144mg/200grbw and continued with GSH dose 25.2mg/200grbw. On the 52nd day, FSH levels were analyzed using ELISA, and the number, morphology and motility of spermatozoon were examined using a digital microscope. Results: The results showed an average FSH level in the KN group (105.42ng/ml SD±64.44), KP (58.88 ng/ml SD± 22.1), P (64.57ng/ml SD±35.8) with a value of p = 0.072. The average number of spermatozoon in the KN group (43.59 million/ml SD ±14.06), KP (26.37 million/ml SD±12.7), P (43.26 million/ml SD±76.15) with a value of p = 0.007. The average normal morphology of spermatozoon in KN group (21.63% SD±10.9), KP (4.65% SD±4.38), P (23.18% SD±12.59) with p = 0.001. The average motility of spermatozoon in the KN group (57.58 million/ml SD± 11.24), KP (34.29 million/ml SD±21.60), P (72.33 million/ml SD±4.072) with a value p = 0.000. Conclusions: Results of this study concluded that the administration of GSH did not significantly increase FSH levels. There is an effect of GSH on improving spermatozoon quality of rat given MSG.